Ensino de relato de evento passado a crianças com transtorno do espectro autista - Damasceno, Fernanda (Universidade Federal de São Carlos, 2022)
From a behavioral perspective, verbal reporting can be understood as a type of tact. The behavior of reporting about an event with correspondence is a skill of great importance in the individual's social development. The present thesis was divided into two studies. Study 1 carried out a literature review that aimed to identify and analyze behavior analysis articles included reporting of past events as a dependent variable and that investigated teaching procedures for establishing this verbal repertoire. These articles were selected for analysis based on the criteria used. The results made it possible to identify gaps and point out possible paths for future studies. Study 2 empirically investigated the effects of a teaching procedure for reporting a past event and presented the elaboration of the modifications made (e.g., type of verbal response requested, categorization task) based on the continuous analysis of the participants' performances exposed to the procedure. The results indicated that learning occurred only after the introduction of a problem-solving strategy (categorization task). The results produced by both studies confirm the need for further investigation into procedures aimed at teaching the reporting of past events and suggest the need for teaching procedures that consider, in their planning, variables related to remembering behavior.
Teaching past event reporting to children with autism spectrum disorder
Keywords: autismo; correspondência; ensino de relato verbal; elato de eventos passados; tato; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM; 4. Educação de Qualidade